1993
DOI: 10.1002/bip.360331003
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive polypeptides: Photochromism and conformation of poly (L‐glutamic acid) containing spiropyran units

Abstract: SYNOPSISSpirobenzopyran units were bound to the side chains of poly (L-glutamic acid) and partially methylated poly (L-glutamate ) s. The modified polymers were found to exhibit "reverse photochromism" in hexafluoro-2-propanol ( HFP ) , so the samples kept in the dark were characterized by an intense absorption band in the visible range of the spectrum, which was completely erased upon exposure to sunlight or irradiation at 500-550 nm.The CD spectra showed that the macromolecules adopted a random coil conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…The latter is generally performed by the condensation between spiro-compounds containing hydroxyl (Ciardelli, Fabbri, Pieroni, & Fissi, 1989) or carboxyl groups (Edahiro, Sumaru, Takagi, Shinbo, & Kanamori, 2006Fissi, Pieroni, Ruggeri, & Ciardelli, 1995Hirakura et al, 2004) and complementary functional groups into the macromolecule. Photo-responsive spiro-compounds have been attached to biopolymers from renewable resources such as polypeptide (Ciardelli et al, 1989;Fissi et al, 1993Fissi et al, , 1995Pieroni, Fissi, Viegi, Fabbri, & Ciardelli, 1992), pullulan (Hirakura et al, 2004), methylcellulose (Arai, Shitara, & Ohyama, 1996) and dextran (Edahiro et al, 2006), through condensation, or chitin (Fu et al, 2008) through graft polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is generally performed by the condensation between spiro-compounds containing hydroxyl (Ciardelli, Fabbri, Pieroni, & Fissi, 1989) or carboxyl groups (Edahiro, Sumaru, Takagi, Shinbo, & Kanamori, 2006Fissi, Pieroni, Ruggeri, & Ciardelli, 1995Hirakura et al, 2004) and complementary functional groups into the macromolecule. Photo-responsive spiro-compounds have been attached to biopolymers from renewable resources such as polypeptide (Ciardelli et al, 1989;Fissi et al, 1993Fissi et al, , 1995Pieroni, Fissi, Viegi, Fabbri, & Ciardelli, 1992), pullulan (Hirakura et al, 2004), methylcellulose (Arai, Shitara, & Ohyama, 1996) and dextran (Edahiro et al, 2006), through condensation, or chitin (Fu et al, 2008) through graft polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Eight-five percent spiropyran-containing poly (L-glutamate), PSG, was synthesised as already described [4]. The chemical structure is reported in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…On the same LB films of PSG, we recorded Circular Dichroism (CD) spectra. Previously acquired CD spectra of dark-adapted and irradiated PSG in HFP solution [4] showed that the spectrum of dark-adapted PSG corresponds to the spectrum of random coil polypeptides with a maximum at 212 nm.…”
Section: Two-dimensional Nano-organized Films Of Psgmentioning
confidence: 99%
“…It has a tremendous demand in sensory [1] as well as biomedical field [2]. This 'smart' compound is able to elicit responsive behaviour on changes in the environment [3]. Light is one of the stimuli that capable of performing those conformational and chemical changes in particular system [4].…”
Section: Introductionmentioning
confidence: 99%